Microstrip interdigital-hairpin bandpass filter / Mohd Rezzuan Nasharudin - Nasharudin, Mohd Rezzuan
This paper deals with a microstrip single layer of inter-digital hairpin. The concept of the Alter is the combination of interdigital and hairpin types of Alter, which the designed used the fundamental idea of coupled lines. The Alter was designed with four sections (four-pole) of Ushaped, hairpin types, which one of each feeds is touching ground via holes such the interdigital filter type. Based on the concept and to illustrate the various possibilities, the circuit layout, simulations, and calculation are presented in this paper. Index